APLIKASI QUIZZME UNTUK EVALUASI PEMBELAJARAN SISWA BERBASIS ANDROID PADA JENJANG SMP - Tri Setyowati, Lisa; Sudargo, Sudargo; Menarianti, Ika (JIPETIK:Jurnal Ilmiah Penelitian Teknologi Informasi & Komputer, 2022)
ABSTRACTThis research was conducted during the current pandemic where all learning cannot be done face-to-face in the classroom and is replaced by virtual means, so an application like QuizzMe is needed to assist teachers in evaluating virtual learning. The purpose of this research is to create a QuizzMe application for learning evaluation media at the junior high school level and to make it easier for teachers to store learning evaluation questions. The development model used is the ADDIE development model. ADDIE can be used for various forms of product development such as models, learning strategies, learning methods, media and teaching materials, the stages of developing learning models are (1) analysis, (2) design, (3) development, (4) implementation and (5 ) evaluation. The system design in the making includes making flowcharts, use case diagrams, activity diagrams, and sequence diagrams. Then implemented in the SQL programming language using the MySQL database. The results showed that the expert validation assessment using a Likert scale obtained an average result by two material expert validators of 97.5% and two media expert validators of 75%, so that the average of the four validators could be declared suitable for use. Then the assessment of the respondents using a Likert scale, obtained an average result of 72% and was declared suitable for use.